La notion de situation dans l'étude des phénomène d'enseignement et d'apprentissage des langues : vers une perspective socio-didactique - Joaquim Dolz; Frédéric Tupin (Recherches en Éducation)
This article is in line with a progression which has given rise to reflections and to several successive publications initiated in 2006. After having tried to extend the boundaries of the concept of situation and of its use in order to understand teaching and learning phenomena in the light of sociology contribution (Tupin, 2006) then having called for a joint comprehension of the "epistemological subject" and of the "social subject", through the organization of a dialogue between didactics and sociology (Tupin & Dolz, 2008), the present article aims at revisiting the stratification of the concept of situation and of its use, from the specific perspective of the co-presence of languages in society, schools and classrooms. This text highlights a set of registers, in which the concept of situation is summoned and contributes to interventionist approaches to language didactics. In this respect, the characteristics of the linguistic material seem to confront the didactic system with the specific object of language knowledge and practice at work in the educational context. The transversal quality of this object which encompasses very different statuses, many contents and significant variations of use, questions the connections to make between classrooms "internal phenomena" and "external phenomena". This heterogeneity which characterizes both the educational situations and their didactic interpretations' must be highlighted through the intersectional approaches of sociolinguistics and language didactics. The next step will be to revitalize a model that will link up through the dialectical movement that binds them, the "internal side" and the "external side" of teaching and learning situations.